DOES REFORM PLAN REALLY WORKS? ASSESSING ENTITY DEVELOPMENT PLAN IN WASIT PROVINCE-IRAQ - Karrar Hameed Altaie; Sabeeh Farhan Laftah; Hayat Jumaa Muhammed (Scholar Express Journals, 2022)
This study aims to assess the effect of some production factors on the funds of entity development plan in Wasit province. Technical (TE) and scale efficiency (SE) were used, as a tools to measure the technical relationship prescribed earlier. This paper utilized a sample of Wasit province district in Iraq between 2006 and 2008. In order to measure this technical relationship, Non-parametric data envelopment analysis (DEA) were used . Results of this paper regarding technical efficiency (TE) has proved that this reform plan project was a big success. In all years of implementation, averages TE in 2006, 2007 and 2008 were 98, 89 and 89 respectively. For scale efficiency, SE scores approved that 25 percent of the studied sample were operating at the optimum Wasit province level. However, 60% of the sample could increase their technical efficiency by increasing their size. All in all, this reform plan approved its feasibility through the study period depending on TE and SE scores
Keywords: Wasit province; efficiency; approved